Employee innovative behavior and workplace wellbeing: Leader support for innovation and coworker ostracism as mediators - Wang, Hui; Chen, Xueshuang; Wang, Hui; Xie, Mingxing (Frontiers in Psychology, 2022)
Introduction Most previous studies focused on the antecedents of employee innovative behavior but rarely examined the outcomes of employee innovative behavior. Moreover, previous studies ignored the relationship between employee innovative behavior and workplace wellbeing. Based on social comparison theory and social exchange theory, this study introduces coworker ostracism and leader support for innovation as mediating variables to explore the “double–edged sword” effect of employee innovative behavior on workplace wellbeing. Methods Based on a sample of 319 employees from Chinese companies, this study used SPSS 26.0 and MPLUS 8.3 to examine the hypotheses. Results Empirical results demonstrate that (a) employee innovative behavior is directly and positively related to workplace wellbeing, (b) employee innovative behavior is indirectly and positively related to workplace wellbeing through leader support for innovation, and (c) the negative association between employee innovative behavior and workplace wellbeing via coworker ostracism is unsupported. Discussion The findings of this study enrich the literature by exploring the double-edged sword effect of employee innovative behavior on workplace wellbeing. The practical implications of this study are that leaders in organizations should give employees innovation support.